Helicobacter pylori CagL Y58/E59 Mutation Turns-Off Type IV Secretion-Dependent Delivery of CagA into Host Cells - Tegtmeyer, Nicole (Public Library of Science, 2014)
The type IV secretion system (T4SS) is a major virulence determinant of the gastric pathogen Helicobacter pylori. The CagL protein is a specialized adhesin of the corresponding T4SS pilus, which establishes initial contact with the integrin β1 receptor on host target cells. Recent studies proposed that Y58 and E59 amino acid polymorphisms in CagL increase the virulence of H. pylori strains by enhanced translocation and phosphorylation of the CagA effector protein. These polymorphisms were therefore correlated with an increased risk of gastric cancer development. Here we show that the Y58/E59 motif, which is located in a loop connecting two α-helices, and corresponding polymorphisms could influence the function of CagL. However, expression of isogenic CagL Y58/E59 variants in H. pylori strain 26695 significantly blocked the translocation and phosphorylation of CagA as compared to complemented wild-type CagL. These results suggest that the function of the T4SS for delivery of CagA is turned-off by the Y58/E59 mutation in CagL. This activity appears to be similar to the one recently described for another T4SS pilus protein, CagY, which is also sufficient to cause gain or loss of T4SS function. These data support the hypothesis that certain mutations in CagL or recombination events in CagY may serve as a sort of molecular switch or perhaps rheostat in the T4SS, which could alter the function of the pilus and "tunes" injection of CagA and host pro-inflammatory responses, respectively.